Inventarisasi Serangga pada Pertanaman Cabai Merah di Kecamatan Air Salek Kabupaten Banyuasin - Arsi Arsi; Wagiyanti Wagiyanti; Suparman SHK; Yulia Pujiastuti; Siti Herlinda; Harman Hamidson; B. Gunawan; Chandra Irsan; Suwandi Suwandi; R Anwar Efendi; S Imam Nugraha; Lailaturrahmi Lailaturrahmi; R Putra Munandar (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Arsi A, Wagiyanti W, Suparman SHK, Pujiastuti Y, Herlinda S, Hamidson H, Gunawan B, Irsan C, Suwandi S, Efendi RA, S Nugraha I, Lailaturrahmi L, Munandar RP. 2020. Inventory of insect insfesting chili cultivation in sub district Air Salek, district Banyuasin, In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Inventory of Insect Infesting Chili Cultivation in Sub District Air Salek, District Banyuasin Capsicum annuum L is one of the important horticultural crops cultivated in Indonesia and has high economic value. Chili plant is never been free from the associated insect activity. This field practice aims to find out the species species and insect population in the red chili crop. The field practice has been carried out at the farmers' chilli crop in Sub District Air Salek, Banyuasin Regency. Insect identification was carried out at the Entomology Laboratory of Plant Pests and Diseases at the Faculty of Agriculture, Sriwijaya University. The implementation was carried out by direct observation using the census method by applying purposive sampling technique and using steiner trap fruit flies. The results showed that the populations of fruit fly in the first land, second and third fields was different for each observation. The fruit flies found were two species i.e. Bactrocera carambolae and Bactrocera umbrosa. There are several insects associated with chili plants, namely Coccineilla transversalis, Menochillus sexmaculatus, Micraspis discolor, Micraspis frenata, Aphis gossypii, Spodoptera litura and Altica cyanae. The number of insect populations in a plant is influenced by biotic and abiotic factors. Whether it's from the condition of the plants around or by the application of pesticides in the chili area.